Analysis of Regional Management Information Systems in the Financial Administration System at the Regional Financial and Asset Management Agency of Donggala Regency - Nurdiana Pratiwi; Rasmi Nur Anggraeni; Rajindra Rajindra (Universitas Muhammadiyah Palu, 2021)
This study aims to determine the use of the Regional Management Information System (SIMDA) in the Regional Financial Administration System at the Regional Financial and Asset Management Agency of the Donggala Regency and the qualitative research method with a phenomenological approach. And the objectives as well as the required inputs and the outputs generated from the processing. Supporting factors for the use of financial SIMDA at the Regional Financial and Asset Management Agency of Donggalau Regency involve employees in special SIMDA training or training held by BPKP as well as through more specific discussions about SIMDA operations, good responses from implementors, and the existence of a team of administrators as supervisors as well as employees. The financial SIMDA administrator team at the Donggala Regency Financial and Asset Management Agency is guided by the results and training modules so that the Regional Management Information System (SIMDA) in the Regional Financial Administration System produces accurate financial results reporting information.